Urban distribution center location: Combination of spatial analysis and multi-objective mixed-integer linear programming - Sopha, Bertha Maya; Asih, Anna Maria Sri; Pradana, Frendy Dimas; Gunawan, Hendra Edi; Karuniawati, Yuni (International journal of engineering business management, 2016)
Location of urban distribution center (UDC) has played an important role in reducing distribution cost, environmental impact, and traffic congestion in urban areas. The article aims at evaluating potential location of UDC for sugar commodity using a combined approach that comprises two stages: spatial analysis and multi-objective mixed-integer linear programming. Results demonstrate that different locations of UDC correspond to different costs and environmental implications. It is suggested that a new UDC for the sugar commodity can be located at the east part of the city outskirt. Using more than two UDCs in the studied case appears to be not economically and environmentally beneficial.